Characteristics of multi strike surface strength of stones, concrete and bricks used for historical structures since Meiji era in Japan - Shogaki, Т.; Inaba, И. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2021)
Historical structures are part of the heritage humankind hands down to posterity. As records, they not only describe past construction technologies, but they also carry information about the social system and culture of their time. Many historical civil engineering structures constructed during and after the Edo era still remain in Japan. Some of these structures, such as the Yokosuka dry docks, played an important role in the fate of the nation (Shogaki, 2014). However, such sites have not been the subject of systematic geotechnical research or publicity. The strength of construction materials at historical sites built since the Meiji era was investigated using the rebound hammer test (JGS 2013) and evaluated with regard to construction age, facility use, and material. The tested materials were rocks (andesite, granite, and sandstone) at 10 sites, concrete at 6, and brick at 3.